Buy and hold is dead how to make money and control risk in any market - Kee, Thomas H.; Safari eBooks (Hoboken, N.J. : J. Wiley & Sons, 2010)
"Buy and Hold Is Dead provides actionable strategies and disciplines, which can be used to earn positive results in any market environment. Money managers rarely outperform the stock market over time, and this has become a sticking point for many people as our uneven economic landscape continues to unfold. This timely guide is designed around a step-by-step educational process in which traders and investors lean how they can protect their wealth and make money regardless of market direction. The goal of Buy and Hold Is Dead is twofold: to dispel old-school investment techniques and to show you how to maximize your returns without sacrificing time or lifestyle and without the use of a money manager"--Resource description page.
The investment rate -- Keep it simple, sweetheart -- Brackish investors and their impending doom -- Golden handcuffs -- Since when has losing less become a winning strategy? -- Redefining balance -- Contemporary Darwinism -- A proactive aversion -- Embracing independence -- Ahead of the curve -- 2009 : return to parity -- Personal balance sheet -- Every day is Tuesday -- The game plan -- Oscillation cycles -- The golden sequence -- Rule-based trading strategies -- Automated trading -- A greater depression -- Welcome to the comfort zone -- A real-life example.
Description based on print version record.
Includes index.
Keywords: Portfolio management; Risk management; Investments; Electronic books